Research into the impact of an imbalanced teaching-academic research evaluation system on the quality of higher education: based on the mediation effect of the sense of belonging to a university - Wang, Xiao-Wu; Zhang, Yi-Cheng; Du, Qiang (Frontiers in Education, 2024)
With the development of institutions of higher learning, the imbalance between teaching and academic research is becoming increasingly prominent, which, if improperly treated, will restrict the development of universities and higher education. This study first analyzes the imbalanced teaching and academic research evaluation system from three aspects, i.e., the evaluation subject, the weight of teaching and academic research in promotion and their predictive effect on the salary. Then, it verifies that such imbalance has suppressed the development of education and teaching in universities. Third, from the perspective of the dual identity unique to the academic occupation, it proposes the mediation effect of the sense of belonging to a university, and verifies statistically that the sense of belonging to a university can significantly weaken the negative impact of imbalances caused by preferring academic research to teaching. Finally, it makes suggestions on how to improve the evaluation system and enhance the sense of belonging among university teachers.